Preparation method of polytetrafluoroethylene composite film with ultralow dielectric loss and high strength
By using interface modifiers and hydrophobic low-dielectric function fillers in PTFE dispersion to form composite fillers, the strength and dielectric loss problems of PTFE composite film materials in the field of high-frequency communication are solved, and high performance and uniformity are achieved Preparation of PTFE composite membrane materials for mass production.
Patent Information
- Application Number
- CN202310798685.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-03
- Publication Date
- 2025-01-07
AI Technical Summary
The existing PTFE composite film materials have problems such as low strength, poor creep resistance and high dielectric loss in the field of high-frequency communication. The traditional preparation process is prone to lead to interface defects and uneven dispersion of fillers, which cannot meet the high-frequency communication and microelectronics fields. Requirements for material properties.
The polytetrafluoroethylene dispersion is used as raw material to form a composite filler slurry by mixing the interfacial modifier and the hydrophobic low-dielectric function filler. The PTFE composite film material is prepared after film formation, drying and sintering, and the interfacial modifier is formed. The liquid bridge connects PTFE rubber particles to improve the dispersion and interface combination of fillers, and realizes film materials with low dielectric loss and high mechanical strength.
The prepared PTFE composite film material has low dielectric loss, high mechanical strength, uniform thickness, wide width, controllable structure, simple process, suitable for large-scale industrial production, overcomes interface defects and high-frequency dielectrics in traditional processes. Loss problem.
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing a polytetrafluoroethylene composite membrane material, and more specifically to a method for preparing a polytetrafluoroethylene composite membrane using a polytetrafluoroethylene dispersion as a raw material, which has the advantages of thin thickness, good uniformity, controllable structure, large width, high strength, good dimensional stability, low dielectric loss, simple equipment and process, and can realize large-scale industrial production. The method belongs to the technical field of high-performance polytetrafluoroethylene composite membrane material preparation. Background Art
[0002] Polytetrafluoroethylene (PTFE) is the most important fluorine-containing polymer, which is polymerized from tetrafluoroethylene. The molecular chain of PTFE is composed of carbon-fluorine units arranged in a strict alternating pattern, with a helical configuration as a whole and a highly symmetrical molecular structure. The carbon atoms are coated by F atoms with a small radius and high electronegativity. The CF bond has a high bond energy (460 kJ / mol) and a short bond distance. Therefore, PTFE has outstanding dielectric properties, chemical corrosion resistance, lubricity and weather resistance. PTFE membrane materials are widely used in electrical and electronic, aerospace, petrochemical, national defense and military, medical and pharmaceutical fields, and are also indispensable and important materials in high-frequency communications and microelectronics.
[0003] However, PTFE has the disadvantages of low strength, poor creep resistance, and easy cold flow under a certain load. In addition, the coefficient of thermal expansion (CTE) is large, up to 13 times that of copper foil. This will lead to material deformation and even cracking when the PTFE membrane material is laminated with copper foil in the field of high-frequency communications. At present, inorganic filler filling is usually used to improve the above inherent defects of PTFE. However, due to the extremely low surface energy of PTFE, it is extremely difficult to form a good interface interaction with inorganic fillers, and there are problems such as uneven dispersion of fillers and easy agglomeration. On the other hand, traditional PTFE film making methods such as turning and calendering are mostly used to prepare pure PTFE membrane materials. The multi-dimensional force fields such as pressure and shear force in the preparation process can easily cause PTFE to debond from the filler surface and produce interface defects. Although some scholars have modified the surface of the filler to improve the interfacial compatibility between the two, the non-polar PTFE surface and the polar surface of the filler usually cause a mismatch in dielectric constant and conductivity, which leads to charge accumulation and local redistribution of the electric field in applications, resulting in interfacial polarization, and further increasing the dielectric loss of the composite material, which will greatly affect the accuracy of high-frequency information transmission and make it difficult to meet the demand for ultra-low dielectric loss materials in the field of high-frequency communications.
[0004] Therefore, with the increasing performance requirements for lightweight, miniaturization and high stability in the fields of high-frequency communications and microelectronics, it is very necessary to develop a method for preparing a polytetrafluoroethylene composite membrane with thin thickness, good uniformity, controllable structure, large width, high strength, good dimensional stability, extremely low dielectric loss, simple equipment and process, and capable of large-scale industrial production. Summary of the invention
[0005] In view of the shortcomings of the existing PTFE composite functional membrane material preparation method and performance, the purpose of the present invention is to propose a preparation method of a PTFE composite functional membrane material with PTFE dispersion as the main raw material. The method first mixes the interface modifier, the synergist and the hydrophobic low dielectric functional filler into a composite filler slurry to form a pre-impregnation and dispersion of the low dielectric functional filler, and then adds the composite filler slurry to the polytetrafluoroethylene dispersion for mixing and dispersion, and prepares the PTFE composite functional membrane material through film forming, drying and sintering. This also becomes a key technical means for improving the dispersibility and interface bonding of the filler in PTFE without additional surface modification of the filler, and maintaining the extremely low dielectric loss of the PTFE composite membrane material. The obtained PTFE composite membrane material has low dielectric loss, high mechanical strength, uniform thickness, large width, controllable structure and excellent performance. At the same time, the method has the advantages of simple preparation process and large-scale industrial production.
[0006] The basic principle of the present invention is: in view of the disadvantages that the traditional PTFE film making methods such as turning and calendering are easy to cause the PTFE and the filler surface to debond and produce interface defects, and the existing filler surface modification is easy to increase the high-frequency dielectric loss of the composite material and cannot meet the high-frequency communication application, the present invention firstly utilizes the "like dissolves like" principle to mix the oily liquid interface modifier with the low dielectric functional filler with hydrophobic and oleophilic properties to form a composite filler slurry, and adds a synergist to increase the wetting and dispersion effect of the low dielectric functional filler, and then adds the composite filler slurry into the PTFE dispersion, and utilizes the interface modifier that is immiscible with water but not with water to form a composite filler slurry. The good affinity of PTFE particles in PTFE dispersion, on the one hand, allows the interfacial modifier to form a stable liquid bridge between PTFE particles through the action of interfacial tension and capillary force, thereby forming a three-dimensional physical network connected by liquid bridges in the PTFE dispersion and significantly improving the film-forming property of the PTFE composite dispersion. On the other hand, since the low dielectric functional filler is stably dispersed in the interfacial modifier, as the interfacial modifier infiltrates the surface of the PTFE particles, the low dielectric functional filler is also stably and well dispersed in the PTFE dispersion, forming a PTFE composite dispersion with stable dispersion of the low dielectric functional filler. In the subsequent film-forming drying and sintering molding process, the low dielectric functional filler can also be stably dispersed in PTFE. Therefore, there is no need to perform additional surface modification on the filler. Only commercially available hydrophobic low dielectric functional fillers can be used to achieve uniform dispersion of the filler in PTFE and successful preparation of ultra-low dielectric loss PTFE composite membrane materials. In addition, when PTFE composite membrane materials are prepared by casting and other methods using polytetrafluoroethylene dispersion, there is no strong stress caused by traditional PTFE turning or calendering, and the interface between PTFE and filler will not be damaged during the molding process. The composite membrane material has fewer defects and high structural uniformity, which can significantly improve the comprehensive performance of the PTFE composite membrane material.
[0007] The present invention is based on the above principle and the technical solution adopted to achieve the above invention object is: adding a hydrophobic low dielectric functional filler to an interface modifier and a synergist to prepare a composite filler slurry, then adding it to a polytetrafluoroethylene dispersion, and preparing a polytetrafluoroethylene composite film through mixing and dispersion, film forming and drying, sintering and winding, characterized in that: (1) The molecular weight of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 500,000 to 2,000,000, and the particle size of polytetrafluoroethylene latex is 150 to 220 nanometers; (2) The interface modifier is a non-polar liquid with a molecular weight of less than 1000 and a three-phase contact angle with polytetrafluoroethylene particles and water of less than 90 degrees and is immiscible with water, including polyorganosiloxanes with a molecular weight of less than 1000, long-chain alkanes, fatty alcohols and aromatic alcohols, such as a mixture of one or more of silicone oil, white oil, n-dodecane, octadecanol and terpineol, and the added mass is 0.01-5% of the solid mass in the polytetrafluoroethylene dispersion; (3) The synergist is an oil-soluble material that can increase the viscosity of the above-mentioned interface modifier and is immiscible with water, such as a mixture of one or more of modified hydrogenated castor oil, organic bentonite, hydrophobically modified acrylate, polyisobutylene, polymethacrylate, and ethylene-propylene copolymer, and the added mass is 0-5% of the mass of the interface modifier; (4) The hydrophobic low dielectric functional filler is a functional filler with a hydrophilic contact angle greater than 90 degrees and a dielectric loss less than 0.002 at 10 GHz, such as a mixture of one or more of hydrophobic SiO2, TiO2, h-BN, CeO2, Al2O3, MgTiO3, etc. The particle size of the hydrophobic low dielectric functional filler ranges from 20 nanometers to 10 microns, and the added mass is 0.1% to 80% of the solid mass of polytetrafluoroethylene; (5) The composite filler slurry is prepared by adding an interface modifier, a synergist and a hydrophobic low dielectric functional filler into a planetary agitator and stirring at a speed of 1000 to 2000 revolutions per minute for 2 to 10 minutes; (6) The mixing and dispersing process comprises the following steps: adding a composite filler slurry to a polytetrafluoroethylene dispersion, stirring the mixture at a speed of 1000 to 2000 revolutions per minute for 2 to 10 minutes using a propeller or planetary agitator, and then stirring the mixture at a speed of 500 to 800 revolutions per minute for 2 to 10 minutes to prepare a polytetrafluoroethylene composite dispersion; (7) The film-forming and drying step is to cast, scrape or spin coat the polytetrafluoroethylene composite dispersion on a suitable substrate material and dry it at a suitable temperature; (8) The polytetrafluoroethylene composite film can be completely peeled off from the base material and rolled up, and the film thickness ranges from 5 to 200 microns.
[0008] The reason why polytetrafluoroethylene with a molecular weight of 500,000 to 2 million is chosen is that polytetrafluoroethylene with a molecular weight that is too small cannot achieve practical film mechanical strength, and a molecular weight that is too large will lead to excessive melt viscosity and difficulty in film formation; the polytetrafluoroethylene latex particle size is 150 to 220 nanometers because a latex particle size that is too small will increase the size of film defects, and a particle size that is too large will be detrimental to the storage stability of the dispersion.
[0009] Silicone oil, paraffin oil, white oil, n-dodecane, octadecyl alcohol, pinene alcohol and other non-polar liquids with a three-phase contact angle of less than 90 degrees with PTFE latex particles and water, immiscible with water and with a molecular weight less than 1000 are selected because after the above non-polar liquids are dispersed in the polytetrafluoroethylene dispersion, small droplets will be formed under stirring. Since the three-phase contact angle of the non-polar liquids with PTFE particles and water is less than 90 degrees, the non-polar liquids have a stronger wettability to the polytetrafluoroethylene particles than water, and will be connected between the polytetrafluoroethylene particles and remain stable, forming a three-dimensional physical network throughout the PTFE dispersion, which will increase the interaction between the polytetrafluoroethylene particles during film formation and improve the defects formed in the polytetrafluoroethylene film during the drying process.
[0010] Modified hydrogenated castor oil, organic bentonite, hydrophobically modified acrylate, polyisobutylene, polymethacrylate, ethylene propylene copolymer and the like are selected as synergists, which are oil-soluble materials that can increase the viscosity of the above-mentioned interface modifiers and are immiscible with water, because on the one hand, they can improve the dispersion effect of the hydrophobic low dielectric functional filler, and on the other hand, since commercially available polytetrafluoroethylene dispersions generally contain surfactants, the presence of which will weaken the effect of the interface modifier, so the synergist is added to the interface modifier to enhance the interface wettability between the interface modifier and the PTFE particles.
[0011] The particle size range of the hydrophobic low dielectric functional filler is selected to be 20 nanometers to 10 micrometers because the particle size within this range has a better dispersion effect with the PTFE dispersion.
[0012] The film forming drying temperature is selected to be 20-80 degrees Celsius, the drying time is 5-60 minutes, the sintering molding temperature is selected to be 350-400 degrees Celsius, and the sintering molding time is 10-60 minutes. The obtained polytetrafluoroethylene film can be up to 1.5 meters wide and 1000 meters long.
[0013] The present invention proposes a method for preparing an ultra-low dielectric loss and high-strength polytetrafluoroethylene composite membrane using a polytetrafluoroethylene dispersion, which does not require additional surface treatment of the filler and only uses commercially available hydrophobic low-dielectric functional fillers to achieve uniform dispersion of the functional filler in PTFE and successful preparation of an ultra-low dielectric loss and high-strength PTFE composite membrane material; The present invention proposes a method for preparing an ultra-low dielectric loss and high-strength polytetrafluoroethylene composite membrane using a polytetrafluoroethylene dispersion, wherein the film forming, drying, sintering and winding of the PTFE composite dispersion are continuously performed, the drying time is as short as 5 minutes, and the molding time is as short as 10 minutes, thereby overcoming the shortcomings of the traditional PTFE membrane material turning or calendering preparation process, which is multi-process, time-consuming and equipment-complex, and the process is simple, time-consuming and can realize large-scale continuous production; The present invention proposes a method for preparing an ultra-low dielectric loss and high-strength polytetrafluoroethylene composite film using a polytetrafluoroethylene dispersion. The entire preparation process has no strong stress, and the film is sintered in a thin film state. The film itself is heated evenly and there is no temperature gradient inside and outside the film. Therefore, the prepared film has higher uniformity and less internal stress than the film product obtained by turning, and has a strong interface effect between PTFE and filler particles, and has excellent long-term use performance, mechanical properties and ultra-low dielectric loss. The present invention proposes a method for preparing an ultra-low dielectric loss and high-strength polytetrafluoroethylene composite film by using a polytetrafluoroethylene dispersion liquid. The PTFE composite film material is prepared by a coating method. The film thickness can be as low as 5 microns, which is suitable for the current use requirements of ultra-thin and high-performance PTFE composite functional membrane materials. The film thickness can be accurately controlled within the range of 5 to 200 microns by adjusting the single coating thickness and multiple coating methods, and the film thickness uniformity is good. The present invention proposes a method for preparing an ultra-low dielectric loss and high-strength polytetrafluoroethylene composite film using a polytetrafluoroethylene dispersion, wherein the interface modifier used can be removed by volatilization or degradation during the drying and sintering process without generating residues and affecting other properties of the composite material. The obtained PTFE composite dispersion has higher storage stability and is less likely to produce stratification. The preparation method proposed by the invention has strong operability and feasibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 Flow chart for preparing polytetrafluoroethylene composite membrane materials.
[0015] Figure 2 Comparison between the composite membrane photo (a) obtained in Example 1 and the composite membrane photo (b) obtained in Comparative Example 1. DETAILED DESCRIPTION
[0016] The present invention is further described in detail below by way of examples. In the following examples, the amount of each component is by mass. It is necessary to point out here that the following examples are only further explanations of the present invention and cannot be construed as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above-mentioned content of the present invention. Example 1
[0017] Content of each component by weight: Component mass fraction Polytetrafluoroethylene dispersion (Shandong Dongyue Polymer Materials Co., Ltd.) 100 Octadecanol (analytical grade) 1.5 SiO2 (average particle size 500nm) 30 The first step is to prepare the materials according to the above proportions; the second step is to mix octadecyl alcohol and SiO2, use a planetary stirrer to stir at a speed of 1000 revolutions per minute for 8 minutes to obtain a composite filler slurry, and then add it to a polytetrafluoroethylene dispersion, use a planetary stirrer to stir at a speed of 1000 revolutions per minute for 10 minutes, and then stir at a low speed of 600 revolutions per minute for 10 minutes to prepare a polytetrafluoroethylene composite dispersion; the third step is to cast the polytetrafluoroethylene composite dispersion on a substrate, dry it at 40°C for 10 minutes, and then sinter it at 365°C for 15 minutes to form it; the fourth step is to peel off the sintered film from the substrate, and the obtained polytetrafluoroethylene composite film has a thickness of 5 microns and a width of 120 cm.
[0018] If the interface modifier is not added, the hydrophobic low dielectric functional filler cannot be dispersed in the aqueous polytetrafluoroethylene dispersion, and the PTFE composite membrane material cannot be prepared for comparison. But this also illustrates the importance of adding an interface modifier. Only by adding an interface modifier can the commercially available hydrophobic low dielectric functional filler be evenly dispersed in the PTFE dispersion without additional filler surface treatment, and the PTFE composite dispersion can form a good film.
[0019] Comparative Example 1 In order to verify the effect of the interface modifier, the interface modifier in Example 1 was replaced with sodium dodecyl sulfate, a surfactant commonly used in the industry, and a polytetrafluoroethylene composite membrane material having the same thickness, the same drying and sintering process as Example 1 was obtained as Comparative Example 1.
[0020] Comparative Example 1: Content of each component by weight: Component mass fraction Polytetrafluoroethylene dispersion (Shandong Dongyue Polymer Materials Co., Ltd.) 100 Sodium dodecyl sulfate (analytical grade) 1.5 SiO2 (average particle size 500nm) 30 In this embodiment, octadecyl alcohol is used as an interfacial modifier. The thickness of the PTFE composite film after casting, drying and sintering is tested to be 5 microns ± 0.1 microns. The thickness of the PTFE composite film obtained in Comparative Example 1 is tested to be 5 microns ± 0.8 microns. In addition, the PTFE composite film obtained in Comparative Example 1 has many holes and filler agglomeration, and a membrane material with a width of 120 cm cannot be obtained, which shows that the PTFE composite film obtained in this embodiment has good structural uniformity ( Figure 2). The tensile properties were tested by a universal mechanical testing machine. The results showed that the tensile strength was increased from 7.2MPa in Comparative Example 1 to 21.7MPa, and the elongation at break was increased from 20% to 180%. The dielectric properties test results showed that the film prepared in this embodiment maintained the original dielectric properties of polytetrafluoroethylene at 10GHz. Due to fewer micro-defects and good interface bonding, its dielectric loss was reduced from 0.0031 to 0.0003 compared with Comparative Example 1. This shows that the uniformity, mechanical strength and dielectric properties of the PTFE composite membrane material prepared in this embodiment have been significantly improved, and can be used in the field of high-frequency communications. Example 2
[0021] Content of each component by weight: Component mass fraction Polytetrafluoroethylene dispersion (Shandong Dongyue Polymer Materials Co., Ltd.) 100 Octadecanol (analytical grade) 2.0 SiO2 (average particle size 500nm) 20 Boron nitride (average particle size 2 μm) 20 The first step is to prepare the materials according to the above proportions; the second step is to mix octadecyl alcohol with SiO2 and boron nitride, use a planetary stirrer to stir at a speed of 1000 revolutions per minute for 8 minutes to obtain a composite filler slurry, and then add it to a polytetrafluoroethylene dispersion, use a planetary stirrer to stir at a speed of 1000 revolutions per minute for 10 minutes, and then stir at a low speed of 600 revolutions per minute for 10 minutes to prepare a polytetrafluoroethylene composite dispersion; the third step is to cast the polytetrafluoroethylene composite dispersion on a substrate, dry it at 40°C for 10 minutes, and then sinter it at 365°C for 15 minutes to form it; the fourth step is to peel off the sintered film from the substrate, and the obtained polytetrafluoroethylene composite film has a thickness of 15 microns and a width of 150 cm.
[0022] If the interface modifier is not added, the hydrophobic low dielectric functional filler cannot be dispersed in the aqueous polytetrafluoroethylene dispersion, and the PTFE composite membrane material cannot be prepared for comparison. But this also illustrates the importance of adding an interface modifier. Only by adding an interface modifier can the commercially available hydrophobic low dielectric functional filler be evenly dispersed in the PTFE dispersion without additional filler surface treatment, and the PTFE composite dispersion can form a good film.
[0023] Comparative Example 2 In order to verify the effect of the interface modifier, the interface modifier in Example 2 was replaced with sodium dodecyl sulfate, a surfactant commonly used in the industry, and a polytetrafluoroethylene composite membrane material having the same thickness, the same drying and sintering process as Example 2 was obtained as Comparative Example 2.
[0024] Comparative Example 2: Content of each component by weight: Component mass fraction Polytetrafluoroethylene dispersion (Shandong Dongyue Polymer Materials Co., Ltd.) 100 Sodium dodecyl sulfate (analytical grade) 2.0 SiO2 (average particle size 500nm) 20 Boron nitride (average particle size 2 μm) 20 The present embodiment adopts octadecyl alcohol as the interface modifier, and the thickness of the PTFE composite film after the casting coating drying and sintering is tested to be 15 microns ± 0.12 microns, and the thickness of the PTFE composite film obtained in Comparative Example 2 is tested to be 15 microns ± 2.0 microns. In addition, the PTFE composite film obtained in Comparative Example 2 has many holes and filler agglomeration phenomena, and it is impossible to obtain a membrane material with a width of 150 cm, showing the good structural uniformity of the PTFE composite film obtained in this embodiment. The tensile properties were tested by a universal mechanical testing machine, and the results showed that its tensile strength was increased from 6.5MPa of Comparative Example 2 to 23.3MPa, and the elongation at break was increased from 32% to 201%. The dielectric properties test results show that the film prepared in this embodiment at 10GHz maintains the original dielectric properties of polytetrafluoroethylene. Due to fewer micro-defects and good interface bonding, its dielectric loss is reduced from 0.0035 to 0.0005 compared with Comparative Example 2. In addition, due to the addition of boron nitride, the thermal conductivity of the composite material in Example 2 is 7.2 W / m·K, while the thermal conductivity of Comparative Example 2 is 2.8 W / m·K due to micro-defects at the interface between PTFE and boron nitride, which has a large interface thermal resistance and degrades the thermal conductive network. This shows that the uniformity, mechanical strength and dielectric properties of the PTFE composite film material prepared in this example have been significantly improved, and can be applied to the field of high-frequency communications. In addition, the good heat dissipation of the composite film material prepared in Example 2 is also a very important advantage in the field of high-frequency communications. Example 3
[0025] Content of each component by weight: Component mass fraction Polytetrafluoroethylene dispersion (Shandong Dongyue Polymer Materials Co., Ltd.) 100 n-Dodecane (analytical grade) 1.5 Polyisobutylene (molecular weight 5000) 0.02 SiO2 (average particle size 1 μm) 30 The first step is to prepare the materials according to the above proportions; the second step is to mix n-dodecane, polyisobutylene and SiO2, use a planetary stirrer to stir at a speed of 800 revolutions per minute for 6 minutes to obtain a composite filler slurry, and then add it to a polytetrafluoroethylene dispersion, use a planetary stirrer to stir at a speed of 1000 revolutions per minute for 8 minutes, and then stir at a low speed of 600 revolutions per minute for 8 minutes to prepare a polytetrafluoroethylene composite dispersion; the third step is to cast the polytetrafluoroethylene composite dispersion on a substrate, dry it at 60°C for 10 minutes, and then sinter it at 370°C for 15 minutes to form it; the fourth step is to peel off the sintered film from the substrate, and the obtained polytetrafluoroethylene composite film has a thickness of 30 microns and a width of 100 cm.
[0026] If the interface modifier is not added, the hydrophobic low dielectric functional filler and the synergist cannot be dispersed in the aqueous polytetrafluoroethylene dispersion, and the PTFE composite membrane material cannot be prepared for comparison. But this also illustrates the importance of adding an interface modifier. Only by adding an interface modifier can the commercially available hydrophobic low dielectric functional filler be evenly dispersed in the PTFE dispersion without additional filler surface treatment, and the PTFE composite dispersion can form a good film.
[0027] Comparative Example 3 In order to verify the effect of the interface modifier, the interface modifier in Example 3 was replaced with sodium dodecyl sulfate, a surfactant commonly used in the industry, and a polytetrafluoroethylene composite membrane material having the same thickness, the same drying and sintering process as Example 3 was obtained as Comparative Example 3.
[0028] Comparative Example 3: Content of each component by weight: Component mass fraction Polytetrafluoroethylene dispersion (Shandong Dongyue Polymer Materials Co., Ltd.) 100 Sodium dodecyl sulfate (analytical grade) 1.5 Polyisobutylene (molecular weight 5000) 0.02 SiO2 (average particle size 1 μm) 30 This embodiment uses n-dodecane as an interface modifier. The thickness of the PTFE composite film after cast coating, drying and sintering is tested to be 30 microns ± 0.2 microns. The thickness of the PTFE composite film obtained in Comparative Example 3 is tested to be 30 microns ± 2.1 microns. In addition, the PTFE composite film obtained in Comparative Example 3 has many holes and filler agglomeration phenomena, and it is impossible to obtain a membrane material with a width of 100 cm, showing the good structural uniformity of the PTFE composite film obtained in this embodiment. The tensile properties were tested by a universal mechanical testing machine. The results showed that its tensile strength was increased from 8.7MPa in Comparative Example 3 to 26.2MPa, and its elongation at break was increased from 31% to 241%. The dielectric properties test results show that at 10GHz, the film prepared in this embodiment maintains the original dielectric properties of polytetrafluoroethylene. Due to fewer micro-defects and good interface bonding, its dielectric loss is reduced from 0.0027 to 0.0003 compared with Comparative Example 3. This indicates that the uniformity, mechanical strength and dielectric properties of the PTFE composite membrane material prepared in this embodiment have been significantly improved, and can be applied in the field of high-frequency communications. Example 4
[0029] Content of each component by weight: Component mass fraction Polytetrafluoroethylene dispersion (Shandong Dongyue Polymer Materials Co., Ltd.) 100 n-Dodecane (analytical grade) 2.0 Ethylene propylene copolymer (molecular weight 600) 0.04 Boron nitride (average particle size 2 μm) 20 MgTiO3 (average particle size 1 μm) 25 The first step is to prepare the materials according to the above proportions; the second step is to mix n-dodecane, ethylene-propylene copolymer, boron nitride and MgTiO3, and use a planetary stirrer to stir at a speed of 1800 revolutions per minute for 10 minutes to obtain a composite filler slurry, and then add it to a polytetrafluoroethylene dispersion, use a planetary stirrer to stir at a speed of 1000 revolutions per minute for 8 minutes, and then stir at a low speed of 600 revolutions per minute for 8 minutes to prepare a polytetrafluoroethylene composite dispersion; the third step is to cast the polytetrafluoroethylene composite dispersion on a substrate, dry it at 80°C for 10 minutes, and then sinter it at 380°C for 20 minutes to form it; the fourth step is to peel off the sintered film from the substrate, and the obtained polytetrafluoroethylene composite film has a thickness of 30 microns and a width of 150 cm.
[0030] If the interface modifier is not added, the hydrophobic low dielectric functional filler and the synergist cannot be dispersed in the aqueous polytetrafluoroethylene dispersion, and the PTFE composite membrane material cannot be prepared for comparison. But this also illustrates the importance of adding an interface modifier. Only by adding an interface modifier can the commercially available hydrophobic low dielectric functional filler be evenly dispersed in the PTFE dispersion without additional filler surface treatment, and the PTFE composite dispersion can form a good film.
[0031] Comparative Example 4 In order to verify the effect of the interface modifier, the interface modifier in Example 4 was replaced with sodium dodecyl sulfate, a surfactant commonly used in the industry, and a polytetrafluoroethylene composite membrane material having the same thickness, the same drying and sintering process as Example 4 was obtained as Comparative Example 4.
[0032] Comparative Example 4: Content of each component by weight: Component mass fraction Polytetrafluoroethylene dispersion (Shandong Dongyue Polymer Materials Co., Ltd.) 100 Sodium dodecyl sulfate (analytical grade) 2.0 Ethylene propylene copolymer (molecular weight 600) 0.04 Boron nitride (average particle size 2 μm) 20 MgTiO3 (average particle size 1 μm) 25 This embodiment uses n-dodecane as an interface modifier. The thickness of the PTFE composite film after cast coating, drying and sintering is tested to be 30 microns ± 0.18 microns. The thickness of the PTFE composite film obtained in Comparative Example 4 is tested to be 30 microns ± 1.89 microns. In addition, the PTFE composite film obtained in Comparative Example 4 has many holes and filler agglomeration phenomena, and it is impossible to obtain a membrane material with a width of 150 cm, showing the good structural uniformity of the PTFE composite film obtained in this embodiment. The tensile properties were tested by a universal mechanical testing machine. The results showed that its tensile strength was increased from 7.9MPa in Comparative Example 4 to 28.6MPa, and the elongation at break was increased from 40% to 268%. The dielectric properties test results show that the film prepared in this embodiment maintains the original dielectric properties of polytetrafluoroethylene at 10GHz. Due to fewer defects and good interface bonding, its dielectric loss is reduced from 0.0025 to 0.0002 compared with Comparative Example 4. This indicates that the uniformity, mechanical strength and dielectric properties of the PTFE composite membrane material prepared in this embodiment have been significantly improved, and can be applied in the field of high-frequency communications.
Claims
1. A method for preparing an ultra-low dielectric loss, high-strength polytetrafluoroethylene composite membrane, wherein a hydrophobic low dielectric functional filler is added to an interface modifier and a synergist to prepare a composite filler slurry, which is then added to a polytetrafluoroethylene dispersion, and a polytetrafluoroethylene composite membrane is prepared through mixing and dispersing, film forming and drying, sintering and winding, wherein: (1) The molecular weight of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 500,000 to 2,000,000, and the particle size of polytetrafluoroethylene latex is 150 to 220 nanometers; (2) The interface modifier is a non-polar liquid with a molecular weight of less than 1000 and a three-phase contact angle with polytetrafluoroethylene particles and water of less than 90 degrees and is immiscible with water, including polyorganosiloxanes with a molecular weight of less than 1000, long-chain alkanes, fatty alcohols and aromatic alcohols, such as a mixture of one or more of silicone oil, white oil, n-dodecane, octadecanol and terpineol, and the added mass is 0.01-5% of the solid mass in the polytetrafluoroethylene dispersion; (3) The synergist is an oil-soluble material that can increase the viscosity of the above-mentioned interface modifier and is immiscible with water, such as a mixture of one or more of modified hydrogenated castor oil, organic bentonite, hydrophobically modified acrylate, polyisobutylene, polymethacrylate, and ethylene-propylene copolymer, and the added mass is 0-5% of the mass of the interface modifier; (4) The hydrophobic low dielectric functional filler is a functional filler with a hydrophilic contact angle greater than 90 degrees and a dielectric loss less than 0.002 at 10 GHz, such as a mixture of one or more of hydrophobic SiO2, TiO2, h-BN, CeO2, Al2O3, MgTiO3, etc. The particle size of the hydrophobic low dielectric functional filler ranges from 20 nanometers to 10 microns, and the added mass is 0.1% to 80% of the solid mass of polytetrafluoroethylene; (5) The composite filler slurry is prepared by adding an interface modifier, a synergist and a hydrophobic low dielectric functional filler into a planetary agitator and stirring at a speed of 1000 to 2000 revolutions per minute for 2 to 10 minutes; (6) The mixing and dispersing process comprises the following steps: adding a composite filler slurry to a polytetrafluoroethylene dispersion, stirring the mixture at a speed of 1000 to 2000 revolutions per minute for 2 to 10 minutes using a propeller or planetary agitator, and then stirring the mixture at a speed of 500 to 800 revolutions per minute for 2 to 10 minutes to prepare a polytetrafluoroethylene composite dispersion; (7) The film-forming and drying step is to cast, scrape or spin coat the polytetrafluoroethylene composite dispersion on a suitable substrate material and dry it at a suitable temperature; (8) The polytetrafluoroethylene composite film can be completely peeled off from the base material and rolled up, and the film thickness ranges from 5 to 200 microns.
2. The method for preparing an ultra-low dielectric loss, high-strength polytetrafluoroethylene composite film according to claim 1, characterized in that The film forming drying temperature is 20-80 degrees Celsius, and the drying time is 5-60 minutes.
3. The method for preparing an ultra-low dielectric loss, high-strength polytetrafluoroethylene composite film according to claim 1, characterized in that The sintering temperature is 350-400 degrees Celsius, and the sintering time is 10-60 minutes.
4. The method for preparing an ultra-low dielectric loss, high-strength polytetrafluoroethylene composite film according to claim 1, characterized in that The polytetrafluoroethylene composite membrane can be up to 1.5 meters wide and 1000 meters long.